Tiktok Live Stream Shopping Information: Consumer Purchase Behavior in Gen Z - Fransiska, Putu Ika; Ida Ayu Oka (International Journal of Science and Society, 2023)
This study aims to influence the quality of information and the credibility of information on purchase intentions with hedonic experience and the use of information as a mediator and affordability of interactivity as a moderator. The population of this study were all TikTok social media users whose exact number is unknown because it always changes every time, with a sample size of 115. Data collection was carried out by distributing questionnaires using the Google form. The data analysis technique used is SEM-PLS. The results of this study indicate that the quality of information, hedonic experience, the usefulness of information has a positive and significant effect on purchase intention. Information credibility has no significant effect on purchase intention. Information quality, information credibility has a positive and significant effect on hedonic experience. The quality of the information has no significant effect on the usefulness of the information. Information credibility has a positive and significant effect on the usefulness of information. Information quality and information credibility have a positive effect on purchase intention with hedonic experience as a mediator. Information quality, information credibility has a positive effect on purchase intention with the use of information as a mediator. Interactivity affordability is not able to moderate the effect of information quality and information credibility on purchase intention.